CHITOSAN ASSISTED SYNTHESIS OF MULTI-LAYERED ZINC CARBONATE HYDROXIDES FOR MASSIVE REMOVAL OF Cu2+ FROM WATER - Liu, Peili; Li, Yao; Xu, Yeping; Qing, Ye; Han, Chengliang (Journal of the Chilean Chemical Society, 2018)
In this paper, the zinc carbonate hydroxide (Zn5(OH) 6(CO2)2, ZCHO) was prepared by a facile hydrothermal method assisted chitosan (CS). The as-prepared product was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TG). Results indicated that every micro-sized ZCHO particle had a multi-layered structure and was composed of many ZCHO nanoplates. The used CS played the role of the template in the formation of well multi-layered ZCHO particles. TG measurements had further indicated that the remained content of CS in the as-prepared ZCHO powders was about 8 Wt.%. The adsorption isotherm results showed that the ZCHO powders with CS exhibited massive removal of Cu2+ from aqueous solution at room temperature. The equilibrium adsorption was well described by the Freundlich isotherm model. Based on the above experimental results, the possible removal mechanism of Cu2+ by the multi-layered ZCHO was proposed.